1991
DOI: 10.1128/jb.173.23.7501-7510.1991
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor mutations in rpoA suggest that OmpR controls transcription by direct interaction with the alpha subunit of RNA polymerase

Abstract: We have isolated mutations in rpoA, the gene encoding the a subunit of RNA polymerase, that specifically affect transcriptional control by OmpR and EnvZ, the two-component regulatory system that controls porin gene expression in Escherichia coli. Characterization of these mutations and a previously isolated rpoA allele suggests that both positive and negative regulation of porin gene transcription involves a direct interaction between OmpR and RNA polymerase through the a subunit. Several of the rpoA mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 43 publications
4
71
1
Order By: Relevance
“…Promoter swap (30) and OmpF overexpression (39) experiments were consistent, at least qualitatively, with the absence of feedback. In addition, transcriptional reporter strains in which either ompC or ompF was disrupted with an insertion of lacZ showed osmoregulation of beta-galactosidase activity (44). However, the conclusions from other studies of ompF deletions were less clear (35,39).…”
Section: Resultsmentioning
confidence: 43%
“…Promoter swap (30) and OmpF overexpression (39) experiments were consistent, at least qualitatively, with the absence of feedback. In addition, transcriptional reporter strains in which either ompC or ompF was disrupted with an insertion of lacZ showed osmoregulation of beta-galactosidase activity (44). However, the conclusions from other studies of ompF deletions were less clear (35,39).…”
Section: Resultsmentioning
confidence: 43%
“…It has been reported that certain amino acid substitutions in the ~ subunit of RNA polymerase severely affect OmpRdependent activation of in vivo ompC and/or ompF transcription [5][6][7], A reconstituted RNA polymerase containing C-terminally truncated ~ subunits does not respond to in vitro transcription activation by certain activator proteins including OmpR [4]. These two independent lines of evidence strongly suggested that OmpR interacts with RNA polymerase (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…the phosphorylation of OmpR results in remarkable enhancement of its DNA-binding ability [3]. Several lines of evidence suggested that OmpR functions through a direct interaction with RNA polymerase [4][5][6][7]. A crucial question then arose, namely, whether or not there is any contact site (or activation site) with RNA polymerase in the primary sequence of the OmpR molecule.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…In addition to the RNAPH s 4 domain, the interactions between the C-terminal domain of the a-subunit of RNAPH and OmpR or some other transcription activators were described [31][32][33][34][35] . To elucidate the initiation steps for transcription activation by PmrA, the interactions between PmrA-DNA and the s 4 or C-terminal domain of the a-subunit of RNAPH remain to be characterized, which is in progress.…”
Section: Discussionmentioning
confidence: 99%